Design of a Smart Device for a Deaf Drivers - Messak Ikbal; Othmani Khaled; Touil Oussama (University of Shahid Hama Lakhdar - El Oued, 2025)
Deaf and hard-of-hearing drivers face significant challenges in recognizing auditory signals on the road, which are essential for safe and responsive driving. This project proposes an intelligent assistive system that captures environmental sounds and classifies them in real time using high-quality microphones and sound cards connected to a Raspberry Pi 4. A machine learning model, built using a Convolutional Neural Network (CNN), is trained to distinguish between critical warning sounds (such as sirens and horns) and irrelevant noise. When a warning sound is detected, the system alerts the driver through a visual LCD screen and a vibration motor. This solution enhances driving safety, independence, and situational awareness for the hearing-impaired community. يواجه السائقون الصم وضعاف السمع تحديات كبيرة في التعرف على الإشارات السمعية على الطريق، والتي تعتبر ضرورية لضمان القيادة الآمنة والمتجاوبة. يقترح هذا المشروع نظاما مساعدا ذكيا يلتقط الأصوات البيئية ويصنفها في الوقت الحقيقي باستخدام ميكروفونات عالية الجودة وبطاقات صوتية متصلة بجهاز Raspberry Pi 4 . يتم تدريب نموذج للتعلم الآلي تم إنشاؤه باستخدام شبكة CNN للتمييز بين أصوات التحذير الحرجة )مثل صفارات الإنذار والأبواق( والضوضاء غير ذات الصلة. عند اكتشاف صوت تحذير، يقوم النظام بتنبيه السائق من خلال شاشة LCD مرئية ومحرك اهتزاز. يعمل هذا الحل على تعزيز سلامة القيادة والاستقلالية والوعي الظرفي لمجتمع ضعاف السمع.
Master's theses: specializing Electrical control
Keywords: Deaf and hard of hearing drivers; Auditory signals; الأصوات البيئية; Microphones; Raspberry Pi 4; CNN; LCD